Catalytic Living Ring Opening Metathesis Polymerisation: The Importance of Ring Strain in Chain Transfer Agents. Issue 43 (11th September 2019) - Liu, Peng; Yasir, Mohammad; Kilbinger, Andreas F. M.
Abstract: A recently developed catalytic living ring opening metathesis polymerisation (ROMP) was investigated using a series of reversible chain transfer agents (CTA) carrying either cyclopentene or cyclohexene rings, differing only in ring strain. All cyclopentene derivatives examined showed significantly faster reaction rates than the corresponding cyclohexene derivatives. This resulted in lower molecular weight dispersities and better control of the molecular weight for the cyclopentene compared to the cyclohexene CTAs. Both Grubbs' second and third generation catalysts could be employed in catalytic living ROMP using cyclopentene CTA derivatives. The kinetics of different CTAs were studied, block copolymers were synthesised and residual ruthenium quantified by ICP‐OES. All polymers were fully characterised by NMR, GPC and MALDI‐ToF mass spectrometry. The new cyclopentene CTAs are readily synthesised in a few straightforward steps and provide faster reaction kinetics than all previously reported reversible CTAs. Abstract : A series of reversible chain transfer agents carrying either cyclopentene or cyclohexene rings were employed in catalytic living ring opening metathesis polymerisation (ROMP). The cyclopentene derivatives show significantly higher reaction rates than the corresponding cyclohexene derivatives, resulting in lower molecular weight dispersities and better control of the molecular weight.